The Drosophila rhomboid gene mediates the localized formation of wing veins and interacts genetically with components of the EGF-R signaling pathway. - Sturtevant, M.A.; Roark, M.; Bier, E. (Genes & Development, 1993)
The rhomboid (rho) gene, which encodes a transmembrane protein, is a member of a small group of genes (ventrolateral genes) required for the differentiation of ventral epidermis in the Drosophila embryo. The ventrolateral genes include spitz, which encodes an EGF-like ligand, and Star. The receptor for spitz may be the gene encoding the Drosophila epidermal growth factor-receptor (Egf-r) because the phenotype resulting from partial loss of function of Egf-r is similar to that of ventrolateral group mutants. Among ventrolateral genes encoding cell-surface or secreted proteins, rho is the only member expressed in a localized pattern corresponding to cells requiring the activity of the ventrolateral pathway. In this paper we provide evidence that spatial localization of rho plays an analogous role in establishing vein pattern in the adult wing. rho is expressed in early wing disc cells likely to be wing vein primordia and later is sharply restricted to developing veins. Flies homozygous for the viable rho(ve) allele have missing veins and rho fails to be expressed in rho(ve) mutant wing discs. Ectopic expression of rho during wing development leads to the formation of extra veins. Gene dosage studies among ventrolateral genes suggest that the rho product (Rho) may facilitate Spi-EGF-R signaling, resulting in activation of RAS. We discuss models for how localized expression of Rho may amplify signaling mediated by ubiquitously distributed ligand and receptor components.